Analisis Marketing Mix Pada Toko Pertanian Dalam Perspektif Etika Bisnis Islam (Studi Kasus Pada Toko Sinar Argo Mandiri Pasuruan) - Pustriani, Pustriani; Saodin, Saodin; Tamam, Tamam (CV. ITTC INDONESIA, 2024)
The purpose of this research is to determine the marketing mix strategy in marketing management at the Sinar Argo Mandiri Shop, Pasuruan. To find out the marketing mix strategy from the perspective of Islamic business ethics at the Sinar Argo Mandiri Pasuruan Shop. Business in the field of agricultural medicine is a business that is quite promising. Like the agricultural medicine shop which is quite large in the Penengahan District area, namely Toko Sinar Argo Mandiri Pasuruan. Toko Sinar Argo Mandiri Pasuruan is a private company operating in the field of agricultural medicine. The people of Penengahan District, most of whom work as farmers, make agricultural medicine businesses very promising and can earn quite large profits. Therefore, entrepreneurs want lots of profits, various strategies and innovations are implemented as steps to achieve the company's desired goals. In Islam it is strictly forbidden to produce or sell anything that destroys good faith and morals, shakes religious values ​​and morals, preoccupies oneself with futile things and takes them away from seriousness, brings them closer to falsehood and keeps them away from the truth, brings the world closer and keeps it away. hereafter. Researchers used a qualitative approach research method. The object of the research is the Sinar Argo Mandiri Shop in Pasuruan. Research data was collected through interviews, documentation and observation methods. The results of this research are that the marketing mix implemented by Toko Sinar Argo Mandiri Pasuruan is in accordance with Islamic business ethics, this can be seen from the absence of deviations that violate the principles of Islamic business ethics in the marketing mix implemented by Toko Sinar Argo Mandiri Pasuruan.